Resilience experiences of non-native speakers of English in US education doctoral programs - Hannah E. Acquaye; Hang Jo; Abdi Gungor (Journal of Pedagogical Research, 2017)
International students, specifically non-native speakers of English, constitute a growing population of the graduate programs in western-based universities like UK, US, and Australia. Despite their document challenges, these students also demonstrate resilience that when appropriately channeled, could promote their success in graduate school.  The purpose of the study was to explore the experiences of non-native speakers of English in education doctoral programs in US.  A qualitative research, specifically a phenomenological approach was used to explore the experiences of non-native speakers of English in US doctoral programs in education. Participants were six doctoral students on F1 visa or equivalent. Semi-structured interviews were conducted, transcribed, and coded. Themes that came out of the codes included knowledge, new experience, and support.   Students used both past knowledge from their home countries to connect with new knowledge. They appreciated new experiences provided by professors and the support from both colleagues and mentors. Implications are discussed.